FEATURES OF VESTIBULAR DYSFUNCTION IN PATIENTS WITH HEREDITARY AND ACQUIRED MOTION SICKNESS - Mishchanchuk, N.S.; Borysenko О.M.; Bezshapochnyi, S.B.; Kuzmenko, S.V. (World of Medicine and Biology, 2020)
It was established that vestibular dysfunction in patients with hereditary and acquired motion sickness plays one of the leading roles in traffic l-oads. Features of vestibular dysfunction in hereditary motion sickness are characteristic for bilateral symmetrical irritative mixed vestibular syndrome of the Ist and the IInd degree in the stage of subcompensation with hearing acuity within the norm symmetrically on both sides. In acquired motion sickness, the features of vestibular dysfunction are manifested by following variability: unilateral irritative peripheral or mixed vestibular syndrome of the IInd degree in the stage of subcompensation or decompensation, as well as asymmetric irritative bilateral mixed syndrome of the IInd degree in the stage of subcompensation with different forms and degrees of hearing loss.It was investigated that unilaterality and asymmetry of irritative vestibular syndromes at the acquired motion sickness is one of signs of basic disease development. Certain differences in vestibular dysfunction increase the efficiency of diagnosis, as well as differential diagnosis of hereditary and acquired motion sickness.